Patient safety on psychiatric wards: A cross‐sectional, multilevel study of factors influencing nurses' willingness to share power and responsibility with patients. (9th August 2017) - Vandewalle, Joeri; Malfait, Simon; Eeckloo, Kristof; Colman, Roos; Beeckman, Dimitri; Verhaeghe, Sofie; Van Hecke, Ann
Abstract: The World Health Organization highlights the need for more patient participation in patient safety. In mental health care, psychiatric nurses are in a frontline position to support this evolution. The aim of the present study was to investigate the demographic and contextual factors that influence the willingness of psychiatric nurses to share power and responsibility with patients concerning patient safety. The patient participation culture tool for inpatient psychiatric wards was completed by 705 nurses employed in 173 psychiatric wards within 37 hospitals. Multilevel modelling was used to analyse the self‐reported data. The acceptance of a role wherein nurses share power and responsibility with patients concerning patient safety is influenced by the nurses' sex, age, perceived competence, perceived support, and type of ward. To support nurses in fulfilling their role in patient participation, patient participation‐specific basic and continuing education should be provided. Managers and supervisors should recognize and fulfil their facilitating role in patient participation by offering support to nurses. Special attention is needed for young nurses and nurses on closed psychiatric wards, because these particular groups report being less willing to accept a new role. Ward characteristics that restrict patient participation should be challenged so that these become more patient participation stimulating. More research is needed to explore the willingness and ability of psychiatric nurses to engage in collaborative safety management with patients who have specific conditions, such as suicidal ideation and emotional harm.